Thrombomodulin and interleukin 6 as potential biomarkers of endothelial dysfunction and inflammation after renal transplant - Mota,Ana Paula L. (2018)
ABSTRACT Introduction: Endothelial dysfunction may contribute to hypercoagulable and inflammation states presents in renal transplant, chronic kidney disease (CKD) and its causes. These disorders can be evaluated by markers, such as thrombomodulin (TM), von Willebrand factor (vWF) and interleukin 6 (IL-6). Objectives: The aim of this study was to assess TM, vWF and IL-6 in renal transplant recipients (RTR) and associate their plasma levels with primary cause of end-stage renal disease (ESRD) and allograft function. Methods: 160 RTR were grouped according to the primary cause of CKD (G1: glomerulopathy; G2: hypertensive nephrosclerosis; G3: diabetic nephropathy; and G4: other causes/unknown etiology); creatinine plasma levels (C1 < 1.4 and C2 ≥ 1.4 mg/dl); and the estimated glomerular filtration rate (eGFR) (R1< 60 and R2 ≥ 60 ml/min/1.73 m2). TM and vWF were determined by the enzyme-linked immunosorbent assay (ELISA) and IL-6 by flow cytometry. The results were presented as median, minimum and maximum; p-value < 0.05 was considered statistically significant. Results: TM levels were significantly higher in the G1 group compared to the others (G1: 8.38; G2: 5.51; G3: 5.88; G4: 6.33 ng/ml, p < 0.0001), and in the R1 group compared to R2 (R1: 6.65; R2: 6.19 ng/ml, p = 0.02). The concentration of IL-6, measured by the mean fluorescence intensity, was higher in C2 group when compared to C1 (C1: 7.9; C2: 13.35, p = 0.03). There was no difference in vWF levels among groups. TM correlated positively with IL-6 and creatinine, and negatively with eGFR. IL-6 also correlated positively with vWF. Conclusion: TM and IL-6 can be identified as potential markers for evaluating renal graft function. TM was more related to the primary cause of CKD compared to vWF and IL-6.